Pengaruh Implementasi Relationship Marketing Terhadap Loyalitas Pelanggan : Survei Pada Pelanggan Perusahaan Da’o Screen Printing Kota Tasikmalaya - Yandie Ramadhany; Depy Muhamad Pauzy; Suci Putri Lestari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the description of Relationship Marketing and Customer Loyalty at Da'o Screen Printing company and to determine the effect of Relationship Marketing on Customer Loyalty at Da'o Screen Printing company. The research method used by researchers is to use descriptive analysis. This research uses a quantitative approach. The type of research used in this research is causal. In this study, the authors conducted direct research on all Da'o Screen Printing customers to obtain data. The sample in this study was 50 people, this is based on saturated sampling technique where the population in this study was 50 people. Researchers will conduct tests using SPSS version 25. Relationship Marketing at Da'o Screen Printing company is currently in a very good classification. Da'o Screen Printing's customer loyalty is currently in a good classification because many customers maintain loyalty at Da'o Screen Printing. Relationship Marketing has a significant effect on Customer Loyalty because if the implementation of Relationship Marketing will increase customers who are loyal to the products provided by Da'o Screen Printing.